Comparison of post-aerobic exercise recovery effect between chocolate milk and plain milk - Chan, Mervyn Huan Hao. (2013)
This study compared the effects of commercially available carbohydrate-protein (CHO-PRO) supplements, namely chocolate milk (CM) and plain milk (PM), on recovery after a prior exercise bout, through post recovery exercise. Eight recreationally active and healthy males in university participated in a randomised, cross-over study that required ingestion of either CM (CHO: 89.6 g, PRO: 41.6 g, FAT: 8 g) or PM (CHO: 42.4 g, PRO: 40 g, FAT: 8 g). In each experimental session, participants ran on a treadmill at ~75% VO2max for 45 minutes or until fatigue (EX1), followed by a 4 hour recovery period where they ingested the test beverage immediately and at 2 hours after EX1. At the end of 4 hours, participants completed a 5 kilometre run at self-selected speeds (EX2). Results showed that time taken to complete EX2 was significantly shorter during CM trial compared to PM trial (CM: 26.8 ± 2.7 min; PM: 28.3 ± 3.4 min; p = 0.03). Participants also exercised at a higher heart rate (CM: 179 ± 7 beats/min, PM: 173 ± 6 beats/min; p = 0.03) during CM than PM trial but had similar ratings of perceived exertion (CM: 14 ± 1, PM: 13 ± 1; p = 0.59). The greater effectiveness of CM found in this study could be due to its greater total caloric and CHO content compared to PM. Future research can compare the effects of CM against other calorically and macronutrient matched CHO-PRO supplements to determine any differences in post-aerobic exercise recovery effects.